Trade and development report : report by the Secretariat of the United Nations Conference on Trade and Development - United Nations Conference on Trade and Development; United Nations Conference on Trade and Development (New York : United Nations, 1984)
This is the fourth annual Trade and Development Report. The focus of this account, which is contained in part I, is on the quantitative impact on trade and development of the functioning of world economy over a relatively short time span. Part II examine the evolution of the trade and payments systems over the last three decades.
Includes bibliographical references
usc 19/02/2019
Loans
Keywords: Commerce; Commerce international; Economic development; Economic history; Developing countries